Lean-Green manufacturing: collaborative content and language integrated learning in higher education and engineering courses - Gaspar, Marcelo (2018)
Lean and Green manufacturing processes aim at achieving lower material and labour costs, while reducing impacts on the environment, and promoting sustainability as a whole. This paper reports on a pilot experiment with higher education and engineering students, exploring the full potential of a collaborative approach on courses integrating the Portuguese Polytechnic of Castelo Branco engineering studies curricula, while simultaneously improving their proÞ ciency in English. Content and Language Integrated Learning (CLIL) has become a key area of curricular innovation since it is known for improving both language and content teacher and student motivation. In this context, instructional design for CLIL entailed tandem work of content (engineering) and language (English) teacher to design learning sequences and strategies. This allowed students to improve not only their language skills in English but also their knowledge in the speciÞ c engineering domain content on green and lean manufacturing processes.